Successful treatment of Heyan Kuntai capsule combined with hormonal therapy in an adolescent with diminished ovarian reserve: a case report - Xue Ao; Ling Xiong; Jialu Zhu; Shiqiao Tan (Journal of Ovarian Research)
Abstract Background Diminished ovarian reserve (DOR), a common female disease, results in reduced fertility and menstrual disorders. Patients without timely treatment often suffer from infertility, ovarian insufficiency, premature ovarian failure and early onset or worsened perimenopausal symptoms caused by estrogen fluctuation or deficiency. However, there is a lack of effective methods to improve ovarian reserve function. Case presentation Here, we report a case of a 13-year-old female with 2-year menstrual disorder. The anti-mullerian hormone (AMH) levels were test twice, with interval of 2 months, yielding results of 0.41 ng/mL and 0.50 ng/mL, respectively. Colour Doppler ultrasound examination showed that there were 4–6 antral follicles bilaterally. The patient was diagnosed with DOR. She was treated with Heyan Kuntai capsule (HYKT) combined with hormonal therapy (HT). Post treament, her AMH level, follicle stimulating hormone level and AFC normalized. Discontinuation of HYKT and continuation of HT alone for 5 months proved ineffective. Consequently, HYKT in combination with HT was continued, leading to normal ovarian reserve function restoration. No adverse reactions were observed during the 4-year follow-up. Conclusions This case highlights the importance of including DOR as a diagnostic consideration in adolescents with menstrual disorders during clinical evaluation. AND combining HYKT with HT might contribute to potential improvements in ovarian function in DOR patients.